2015
DOI: 10.1016/j.jjcc.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Association between estimated glomerular filtration rate and peripheral arterial disease

Abstract: An advanced stage of CKD is independently and significantly associated with the presence of PAD. Targeted screening with ABI measurement can be beneficial in patients with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…Estimates from the Third National Health and Nutrition Examination Survey (NHANES III) showed that the prevalence of PAD in patients with CKD is 24% . The previous study also showed a more advanced stage of CKD significantly correlated with the presence of PAD . Consistent with prior reports, our study revealed a high PAD prevalence of 24.4% in patients with eGFR < 60 mL/min/1.73 m 2 using CKD‐EPI formula, which doubled the risk of PAD (15.4%) in participants with eGFR higher than 60 mL/min/1.73 m 2 .…”
Section: Discussionsupporting
confidence: 91%
“…Estimates from the Third National Health and Nutrition Examination Survey (NHANES III) showed that the prevalence of PAD in patients with CKD is 24% . The previous study also showed a more advanced stage of CKD significantly correlated with the presence of PAD . Consistent with prior reports, our study revealed a high PAD prevalence of 24.4% in patients with eGFR < 60 mL/min/1.73 m 2 using CKD‐EPI formula, which doubled the risk of PAD (15.4%) in participants with eGFR higher than 60 mL/min/1.73 m 2 .…”
Section: Discussionsupporting
confidence: 91%
“…The BP measurements of both arms were done simultaneously using the ankle-brachial BP index (ABI) form of automatic device (Omron Healthcare, Kyoto, Japan) [14,15]. Measurements were taken in the sequence of right arm, left arm, right ankle, and left ankle and repeated twice in the supine position with appropriately sized cuffs.…”
Section: Blood Pressure Measurementsmentioning
confidence: 99%
“…[22][23][24] Given that eGFR is simple and easy to calculate, eGFRcr is the most prevalent index for assessing overall kidney function. A previous study, however, proposed that eGFRcr is often overestimated in individuals with reduced muscle mass.…”
Section: Gfr and Muscle Sarcopeniamentioning
confidence: 99%